SYNTHESIS AND ANTIPLASMODIAL ACTIVITY TESTING OF (1)-N-ALKYL- AND (1)-N-BENZYL-6-NITRO-1,10-PHENANTHROLINIUM SALTS AS NEW POTENTIAL ANTIMALARIAL AGENTS - Ruslin Hadanu; Sabirin Mastjeh; Jumina Jumina; Mustofa Mustofa; Eti Nurwening Sholikhah; Mahardika Agus Wijayanti (Universitas Gadjah Mada, 2012)
The synthesis of 5-nitro-1,10-phenanthroline hydrate 2 derivatives from 1,10-phenanthroline monohydrate as starting material has been carried out. The 5-nitro-1,10-phenanthroline hydrate 2 was obtained through nitration reaction using H2SO4 and HNO3 as catalyst and reagent, respectively. Synthesis of (1)-N-alkyl-6-nitro- and (1)-N-benzyl-6-nitro-1,10-phenanthrolinium have been prepared using dimethyl sulphate (DMS), diethyl sulphate (DES), benzyl chloride, benzyl bromine, and benzyl iodide. The reagents of benzyl bromine, and benzyl iodide were synthesized from benzyl chloride using NaBr in ethanol absolute and NaI in acetone, respectively. The five compounds of 5-nitro-1,10-phenanthroline hydrate 2 derivatives were conducted to evaluate the in vitro antiplasmodial activity. The in vitro antiplasmodial was evaluated on strains of Plasmodium falciparum FCR-3 resistant chloroquine and D10 sensitive chloroquine. The 50% inhibition concentration (IC50) of the five compounds ranged from 2.41±1.41 to 0.07±0.01 μM. The results showed that the (1)-N-benzyl-6-nitro-1,10-phenanthrolinium iodide had highest antiplasmodial activity.